Synthetic data generation for a longitudinal cohort study – evaluation, method extension and reproduction of published data analysis results - Kühnel, Lisa; Schneider, Julian; Perrar, Ines; Adams, Tim; Moazemi, Sobhan; Prasser, Fabian; Nöthlings, Ute; Fröhlich, Holger; Fluck, Juliane (Scientific reports, 2024)
Access to individual-level health data is essential for gaining new insights and advancing science. In particular, modern methods based on artificial intelligence rely on the availability of and access to large datasets. In the health sector, access to individual-level data is often challenging due to privacy concerns. A promising alternative is the generation of fully synthetic data, i.e., data generated through a randomised process that have similar statistical properties as the original data, but do not have a one-to-one correspondence with the original individual-level records. In this study, we use a state-of-the-art synthetic data generation method and perform in-depth quality analyses of the generated data for a specific use case in the field of nutrition. We demonstrate the need for careful analyses of synthetic data that go beyond descriptive statistics and provide valuable insights into how to realise the full potential of synthetic datasets. By extending the methods, but also by thoroughly analysing the effects of sampling from a trained model, we are able to largely reproduce significant real-world analysis results in the chosen use case.